The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1055/s-0032-1325330
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Shear Wave Ultrasound Elastography for Neck Lesions Identified in Routine Clinical Practice

Abstract: Intra- and inter-rater reliability of SWE is fair to excellent according to ICCs. SWE reliability is influenced appreciably by acquisition technique. Nevertheless, CORs for SWE are not negligible. To determine whether these results are acceptable clinically, further research is required to establish SWE stiffness values of normal and pathological tissues in the neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 29 publications
4
42
1
2
Order By: Relevance
“…The present results were slightly higher than in previous studies showing an interoperator ICC of 0.72-0.97 and intraoperator ICC of 0.78-0.98. 28,[36][37][38] On the other hand, the reproducibility of strain sonoelastography is considered to be dependent on the operators' skill. Previous studies examining in vivo the muscle, kidney and heart indicated an interoperator ICC of 0.72-0.89 and intraoperator ICC of 0.47-0.96.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present results were slightly higher than in previous studies showing an interoperator ICC of 0.72-0.97 and intraoperator ICC of 0.78-0.98. 28,[36][37][38] On the other hand, the reproducibility of strain sonoelastography is considered to be dependent on the operators' skill. Previous studies examining in vivo the muscle, kidney and heart indicated an interoperator ICC of 0.72-0.89 and intraoperator ICC of 0.47-0.96.…”
Section: Discussionmentioning
confidence: 99%
“…28,[34][35][36][37][38] Regarding the masseter muscle, its hardness in patients with temporomandibular disorder accompanied by myofascial pain has been clarified to be greater than those of healthy volunteers. 11,12,14 The difference between the left and right hardness of the masseter muscles in patients was greater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, elastography is thought to add valuable information about the tissue stiffness and, consequently, the potential malignancy of a lesion. Although strain elastography is often described as operator dependent because of the manual compression performed during the measurement, more recently developed techniques for SWE are supposed to be independent of the examiner because the push pulses are generated automatically (Badea et al 2013a;Bhatia et al 2012aBhatia et al , 2013aBhatia et al , 2013b. Numerous descriptions of successful application of SWE have been reported, for example, in the liver, thyroid, breast and prostate (Au et al 2014;Beland et al 2014;Cebi Olgun et al 2014;Fukuhara et al 2014;Lin et al 2014;Woo et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest ARFI elastography as a useful tool in the differentiation of malign and benign thyroid nodules with or without in combination with gray-scale ultrasonography fi ndings [10][11][12].…”
Section: Discussionmentioning
confidence: 99%